Why have not EU accession countries yet accessed knowledge based society : What social sciences cand do? A case of Croatia - Švarc, Jadranka (Array, 2004)
The main thesis of the paper is that moving towards knowledge-based society is deeply socially and politically rooted. To support the thesis the authors analyze the social context of R&D and innovation activities in Croatia − an East European country in transition. The state of social and political "semi-modernism" in Croatia prevents the recognition of innovation and technological change as the main driving forces of the new economy. It also prevents the establishment of the national innovation system (NIS) which is the environment necessary for structural changes towards the new economy. The main components of the Croatian NIS are described to illustrate the influence of semi- modernism and the failures of the de-industrializing intellectual and political elites. The authors compare the two models, the national innovation system and the triple helix (TH). They find out the striking similarity between NIS used to describe the transformation of economy towards innovation based competition and the concept of the Triple helix used in social sciences as an useful theoretical and analytical framework for studying the social process of that same "endless transition" towards the knowledge-based society. The authors conclude that the role of TH in social science closely corresponds to the role of NIS in economic sciences. The TH model of evolutionary convergence of the three helices towards economic growth resembles the idea of managing innovation and designing growth by building NIS. Finally, the paper argues that the concept of TH is suitable even for the less developed countries because today the transfer and imitation of innovation are knowledge intensive as well as network activities. If nothing else, the Triple-helix model of communication between helices is a democratic way of setting up national development priorities that Croatia, a semi-modern society, lacks.